Analysing Dominant Returns: Skill Development and Fulfilment in SDG Solution Projects in Eastern Malaysia - Nik Hasif; Muhamad Azwan; Muhammad Rahimi; Othman, Norfatiha; Norhana; Talib, Azlizan (Journal of Technical Education and Training, 2024)
Despite numerous solution funded by the All-Party Parliamentary Group on the Sustainable Development Goals (APPGM-SDG) in the Eastern regions of Malaysia, there is a lack of comprehensive understanding regarding the impact of different domains of Returns on Value (ROV) on beneficiaries, particularly within the context of TVET. The initiated solution projects often align with the objectives and principles of TVET, since they involve skills training, work-based learning, curriculum development, promotion of lifelong learning, community engagement, and alignment with SDG. The objective of this paper is to analyse the impact of the two predominant domains on beneficiaries and identifies the critical contributing factors. Using a mixed-method approach, this study categorizes sixteen solution projects from six different Parliamentary constituencies into two groups. The findings demonstrate that the domains of skill enhancement (“Clear”) and deep fulfilment (“Deep”) remain dominant in both groups, whether through self-reporting by solution providers, or through validation processes. Numerous pivotal elements have contributed to these dynamics, encompassing the local socio-economic backdrop, the locality, and the inherent characteristics of the APPGM-SDG initiatives. These findings also highlight the critical importance of integrating comprehensive skill development and fostering personal profound connection to achieve sustainable development, suggesting that future APPGM-SDG initiatives should continue to prioritize these elements to maximize their impact particularly in Malaysia’s Eastern zone.